2020
DOI: 10.1111/irv.12723
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical features, and resource utilization associated with respiratory syncytial virus in the community and hospital

Abstract: Background: The epidemiology, clinical features, and resource utilization of respiratory syncytial virus (RSV) cases in the community and the hospital are not fully characterized. Methods:We identified individuals of all ages with laboratory-confirmed RSV from two sources, a community cohort undergoing surveillance for acute respiratory infections (ARIs) and hospitalized patients from the same geographic area of New York City between 2013 and 15. The epidemiology, clinical features, and resource utilization (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Asymptomatic or mild RSV reinfections are common in adult life [10], with more severe manifestation in immunocompromised individuals [11], patients with cardiopulmonary diseases, and the elderly [12]. The increasing evidence on RSV in the elderly suggests that the impact of the disease is non-negligible, particularly in people with underlying comorbidities, and is comparable to that of non-pandemic influenza [12][13][14].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic or mild RSV reinfections are common in adult life [10], with more severe manifestation in immunocompromised individuals [11], patients with cardiopulmonary diseases, and the elderly [12]. The increasing evidence on RSV in the elderly suggests that the impact of the disease is non-negligible, particularly in people with underlying comorbidities, and is comparable to that of non-pandemic influenza [12][13][14].…”
Section: Key Pointsmentioning
confidence: 99%
“…Overall, RSV infection has been recognised as a disease with a considerable impact in the community and on hospital services that requires prevention in young children and older adults [14]. Currently, the only preventive strategy is passive immunisation since active immunisation is not yet available.…”
Section: Key Pointsmentioning
confidence: 99%
“…The identified viral agents included all the respiratory viruses commonly circulating in the community as well as in the hospital setting, namely FLU A and B viruses, RHV/EV, HCOV, RSV, HMPV, PIV and ADV, as already reported by other authors [8][9][10]. It is well known that the knowledge and monitoring of the prevalence of respiratory viruses in hospital settings is very important, as the impact of these infections in hospitalized patients can have more serious consequences than in the general population [1][2][3][4][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 92%
“…For instance, the respiratory syncytial virus exhibits notable seasonal distributions, namely, beginning in early autumn, peaking at the end of November or in early December, and gradually decreasing in spring. However, adenovirus, influenza, and human parainfluenza virus were more frequently detected in the spring and summer months, between March and August [ 25 , 26 ]. A study on the admission of children with respiratory diseases in Beijing showed that the most common diagnosis (86.11%) in the adenovirus-positive cases was pneumonia, which was accompanied by common signs and symptoms of fever and cough [ 14 ].…”
Section: Discussionmentioning
confidence: 99%